2018
DOI: 10.31234/osf.io/3mv26
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond Reporting Statistical Significance: Identifying Informative Effect Sizes to Improve Scientific Communication

Abstract: Transparent communication of research is key to foster understanding within and beyond the scientific community. Increased focus on reporting effect sizes in addition of p-value based significance statements may improve scientific communication with the general public. Across two studies (N = 446), we compared informativeness ratings for five effect sizes, Bayes Factor and commonly used significance statements. Results showed that Cohen’s U3 was rated as most informative. For example, 77% of participants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In our opinion, standardized effect sizes can be useful tools for interpreting data when thoughtfully employed by the scientists reporting them. However, sport and exercise scientists should be careful when selecting the appropriate SMD or effect size, and ensure that their choice effectively communicates the effect of interest ( Hanel & Mehler, 2019 ). Herein, we will discuss things to consider when reporting an SMD, and we will close by providing general recommendations and examples that we believe sport and exercise scientists will find useful.…”
Section: Should I Report a Standardized Mean Difference?mentioning
confidence: 99%
“…In our opinion, standardized effect sizes can be useful tools for interpreting data when thoughtfully employed by the scientists reporting them. However, sport and exercise scientists should be careful when selecting the appropriate SMD or effect size, and ensure that their choice effectively communicates the effect of interest ( Hanel & Mehler, 2019 ). Herein, we will discuss things to consider when reporting an SMD, and we will close by providing general recommendations and examples that we believe sport and exercise scientists will find useful.…”
Section: Should I Report a Standardized Mean Difference?mentioning
confidence: 99%
“…CLES is particularly useful because it directly conveys the direction and variability of change scores without suggesting that the mean difference itself is small or large. Further, current evidence would suggest that the CLES is easier for readers to comprehend than a signal-to-noise SMD (Hanel and Mehler, 2019).…”
Section: Alternative To the Signal-to-noise Standardized Mean Differencementioning
confidence: 87%
“…Going back to our earlier example (d z = 11.62 and 0.25 respectively), the CLES would be approximately > 99% and 59.9%, or the probability of a randomly sample individual undergoing an improvement is > 99% or 59.9% for intervention 1 and 2, respectively. As Hanel and Mehler (2019) demonstrated, the CLES may be a more intuitive description of the signal-to-noise SMD.…”
Section: Recommendations For Reporting Effect Sizesmentioning
confidence: 96%
See 1 more Smart Citation
“…), results such as "sprint speed increased (d = 0.47)", or "Hedge's g indicated the effect was large" we suspect are not easily interpreted by coaches, practitioners, or athletes. In fact, some research has shown that though non-scientists find certain standardised effect sizes more 'informative' than others, 38 most are relatively unim-pressed by even 'large' standardised effects 39 . The use of standardised effect sizes likely makes decision making difficult regarding the problem that a coach is looking to solve and ultimately is counterintuitive to the goal of sports scientists.…”
Section: Barriers To Answering This Question (Between Person) Correlamentioning
confidence: 99%